2002
DOI: 10.1248/jhs.48.130
|View full text |Cite
|
Sign up to set email alerts
|

Development of an in vitro Environmental Monitoring System by Using Immune Cells.

Abstract: Phagocytic abilities between casein-induced Sprague-Dawley (SD) rat macrophage and kidney macrophage of fish were compared. First of all, latex bead phagocytosis abilities of macrophages from rat and fish by the same water sample were compared. In vitro exposure of the water samples to the induced SD rat macrophages for 4 hr at concentrations ranging from 10 × to 80 × of the water sample reduced the latex bead phagocytosis of the macrophages with concentration dependency. This result was similar with that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Macrophage was separated from the head kidney following the modification of the method by Shim, Jung, Chung, and Choung (), which was as follows: the head kidney was removed from the fish aseptically. After washing twice with Hank's balanced salt solution, the head kidney was cut into small fragments by ophthalmic scissors.…”
Section: Methodsmentioning
confidence: 99%
“…Macrophage was separated from the head kidney following the modification of the method by Shim, Jung, Chung, and Choung (), which was as follows: the head kidney was removed from the fish aseptically. After washing twice with Hank's balanced salt solution, the head kidney was cut into small fragments by ophthalmic scissors.…”
Section: Methodsmentioning
confidence: 99%
“…The usefulness of immune assays developed in laboratory fish models as monitors of pollution effects on wild fish has recently been validated by Zelikoff et al (2002). A further recent development of note is the observation by Shim et al (2002) that the phagocytic abilities of macrophages of Sprague-Dawley rats and fish (Cyprinus carpio and Carassius auratus) respond similarly to exposure to polluted water. This led the authors to propose that the greater availability of rat macrophages would make them more useful than fish macrophages as a monitor of water pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the evidence is lacking to draw superior sensitive species in immunotoxic detection. Shim et al 36 used phagocytosis of rat macrophages to indicate the pollution levels of several rivers in southern Korea. They found that 40-fold concentrated water obviously inhibited phagocytosis (45−49%), which was close to our findings.…”
Section: Effects Of the Water Sample Extracts On The Phagocytic Activ...mentioning
confidence: 99%